The pedagogical recognition of archaeological heritage: case Turmequé, Boyacá - Benavides Gordo, Jaime Andrés (Universidad de Boyacá, 2021)
Defining the archaeological potentials of the municipalities in Colombia is a difficult task due to the misinformation, the high costs it generates and the fears of property owners when it comes to reporting and registering an archaeological site. However, there are participatory and pedagogical methodological alternatives that allow the recognition and socio-educational management of archaeological heritage, which resort to interdisciplinary exercises that link social actors and guarantee the appropriation of heritage. In the case of Turmequé, five key social actors in the protection and safeguarding of property were recognized, who in turn allowed the identification of 56 movable property, 28 real estate and 7 sites with rock art, consolidating a first inventory and an archaeological zoning of the municipality that allows defining the guidelines for its management and conservation from the institutional articulation, as evidenced in this research article.